2020
DOI: 10.1177/0888406420978606
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Preparation in Communication Instruction for Students With Extensive Support Needs

Abstract: In this investigation, we surveyed 51 faculty members who were involved in teacher preparation programs in the area of extensive support needs (ESN) across a range of institutions of higher education. We asked participants to respond to questions related to the quality and quantity of program content focused on communication instruction and supports for students with ESN. Overall, findings indicated variability in the quality and quantity of teacher preparation–related communication instruction. In addition, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Ahmad, A. R., & Farley (2013) added that the current supervision is no longer aimed at merely checking or evaluating the teachers' performance, but rather leads to technical guidance which in turn leads to continuous teacher development. This is a form of guidance for teachers, including teachers for special education, to improve their teaching skills through various methods such as class visits, workshops, seminars, and training that help fulfill the teachers' needs (Pennington et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmad, A. R., & Farley (2013) added that the current supervision is no longer aimed at merely checking or evaluating the teachers' performance, but rather leads to technical guidance which in turn leads to continuous teacher development. This is a form of guidance for teachers, including teachers for special education, to improve their teaching skills through various methods such as class visits, workshops, seminars, and training that help fulfill the teachers' needs (Pennington et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This media provides an opportunity for users to share layers directly from the software and make online videos so that teachers and students can make live video shows [26]. Online learning of the content aspect can use email too.…”
Section: Technologymentioning
confidence: 99%
“…Communication skills are essential to enjoying a self-determined life, as they are required to access a range of learning opportunities, develop meaningful relationships, and control one’s exposure to preferred and nonpreferred experiences (Pennington et al, 2021). Students with extensive support needs (ESN) often have difficulty acquiring these indispensable skills.…”
mentioning
confidence: 99%
“…Pennington et al (2021) suggested several potential barriers to teachers’ provision of communication support for students with ESN, including the potential abdication of instructional responsibility to related services providers (e.g., speech language pathologists [SLPs]); limited access to technical assistance and support for implementing augmentative and alternative communication (AAC) systems; and practical barriers related to collaboration, staff turnover, and lack of administrative support. They also suggested that teachers might have inadequate preparation in communication programming.…”
mentioning
confidence: 99%
See 1 more Smart Citation